Evaluation on performance of some Sorghum bicolor cultivars as forage resources in the dry land with dry climate - Sajimin Sajimin; Nurhayati D. Purwantari; Sarjiman Sarjiman; Sihono Sihono (Indonesian Center for Animal Research and Development (ICARD), 2017)
The aim of this study was to evaluate the performance of several Sorghum bicolor cultivars as forage on a dry land with pH of 5.4, N of 0.08%; C/N of 9%, P of 0.06% and K of 0.01%. Nine cultivars of S. bicolor (Super 1, Super 2, Numbu, Kawali, G2, G5, PAC 537, PAC 593 and PAC 501) were evaluated. Plot size was 16 m2 with space planting of 15 x 75 cm. The experimental design used was randomized block design with three replications. Parameters observed were plant height, time of flowering, forage production and quality. The result showed that the primary plant growth was not different in all cultivars. In the 65 days old primary plant, the Super 2, PAC 537 and Kawali had no flower yet. Biomass production varied in primary plant between cultivars of 11.35 - 26.17 kg/16 m2. The highest biomass production was obtained in PAC 537 of 26.17 kg/16 m2 (16.34 t/ha) which were significantly higher than G2 of 11.35 kg/16 m2 (7.09 ton/ha) and was not significantly different with other cultivars. In the 45 days ratoon I, Super 2, G5 and Super 1 showed faster growth. Biomass production increased in the ratoon I around 19.88 kg/16 m2 (12.42 ton/ha). PAC 537 produced the highest biomass of 30.14 kg/16 m2 (18.84 ton/ha) and was not significantly different with other cultivars, except with the G2. Biomass production of ratoon II decreased around 1.83 kg/16 m2 (1.14 t/ha)–4.77 kg/16 m2 (2.98 t/ha) and increased in the ratoon III of 15.72 kg/16 m2 (9.82 t/ha)–26.05 kg/16 m2 (16.28 t/ha). The quality of forage ratoon I was better compared to the primary plant with the lowest one was in ratoon II. It could be concluded that Super 1, Super 2 and PAC 537 cultivars might be recommended as potential forage.